Estrategias de aprendizaje cooperativo para fortalecer el desarrollo participativo en clases con los estudiantes de 4to año de EGB de la UE Emigdio Esparza Moreno, Babahoyo. 2022 - Villamar Muñoz, Angie Carolina (2022)
This research has the purpose of analyzing the cooperative learning strategies in the participatory development in classes, the influence on the teaching and learning processes in the students of the educational environment observed in the pre-professional practices, when doing this research it would be verified as the strategies of learning would help in the development of the programmed classes and in the learning processes in the students of the educational environment. In the realization of the pre-professional practices carried out in the Educational Unit "Emigdio Esparza Moreno" of the Babahoyo canton, it was possible to notice the lack of attention and cooperation of the students in their learning and academic development, through this the observational method was used investigative-analytical, through a questionnaire of questions, in which the variations of students and teachers in the participatory learning process are detailed. This research was born through the observation carried out in the Educational Unit "Emigdio Esparza Moreno", in which the crisis of cooperative learning strategies is evidenced, in the participatory development of the students and for that reason they have a low academic performance. It is necessary to undertake actions and assume positive activities to the rescue of a healthy coexistence among the members of the educational institution so that the students acquire new knowledge, this project seeks to generate a positive effect in the formation of people.